So fades the light [videorecording (DVD)] - Get Super Rad; Lotz, Kiley; Solomom, D. Duke; Reynolds, Ny'ea; Swift, William (Gravitas Ventures, 2025)
As a child, Sun was worshipped by an extremist gun cult. Fifteen years later, she travels back to the compound for closure. But little does she know, the cult's former leader has been released from prison and is headed the same direction.